Inovasi Bahan Ajar Baca Puisi melalui Multimedia 3D Flipbook - Yusra D (Universitas Batanghari Jambi, 2022)
The purpose of this study is to describe the innovation of poetry reading teaching materials through 3D Flipbook multimedia. The method used in the research is descriptive procedural research method. The reference is ADDIE model development research. What is described is 3D multimedia Flipbook for learning to read poetry. Data collection was carried out using a closed questionnaire. There were 24 respondents, who were seventh semester students of the Indonesian Language and Literature Education Study Program, FKIP Jambi University. The results of the study illustrate that the 3D Flipbook multimedia when used by lecturers in teaching is an actual medium, brings innovation, has an appeal, and makes it easier to follow the lecture flow and examples. The average respondent's assessment for all aspects assessed is 4.60. Aspects of media appearance were assessed with an average of 4.70 (decent category); the content aspect of poetry reading material is assessed with an average of 4.50 (very decent category); and the learning aspect was assessed with an average of 4.60 (very feasible category).